EFFECTS OF THERMOMECHANICAL TREATMENTS ON THE THERMAL EXPANSION COEFFICIENT OF SOME ALUMINIUM ALLOYS (Sciences & Technology. A, exactes sciences, 2007)
The aim of this study was the determination of the thermal expansion coefficient α (T) in relation to the temperature of the three following aluminium alloys:- Al-6%Zn-3%Mg obtained by conventional ingot casting- Al-0.5%Mg-0.88%Si obtained by Direct Cast Casting- Al-1.88%Mn-0.8%Mg obtained by Twin Roller Melt SpinningThese alloys have undergone various thermal and mechanical conditions.The main results show that the Al-6%Zn-3%Mg alloy exhibits a very weak anisotropy meanwhile that Al-Mg-Si and Al-Mn-Mg alloys exhibit, on the contrary, a quite strong anisotropy on the curves of α (T).